Estimation of sea-ice thickness in Ross and Weddell Seas from SSM/I brightness temperatures - Aulicino G.; Fusco G.; Budillon G. (2012)
In polar regions, interactions between atmosphere and ocean are strongly influenced by the presence/absence of the ice cover and by its thickness. Since satellite passive microwave observations became available in the 1970s, significant progress has been made in the study of snow depth and sea ice concentration and extent in these regions. Estimating sea ice thickness instead, turned out to be considerably more difficult. In this work, a new sea ice thickness algorithm (SIT) combines brightness temperature polarization difference and ratio values in an empirical approach to obtain sea ice thickness for seasonal ice up to a thickness of 1 to 1.5 m during freezing conditions. A series of filters accounts for open water, new ice and snow on sea ice. Our sea ice thickness estimates agree within their uncertainties with sea ice thickness derived from National Ice Center ice charts and derived from Antarctic Sea Ice Process & Climate (ASPeCt) project ship-based thickness observations. We observe higher correlations in the Ross Sea (0.9) than in the Weddell Sea (0.8), probably because of the limited data collected in the Weddell area. Moreover, the sea ice thickness gradient downstream of the big Ronne-Filchner Ice Shelf, Ross Sea and Terra Nova Bay polynyas is depicted in both daily and monthly maps of the sea ice thickness distribution. Consequently, we applied the SIT algorithm to estimate sea ice thickness for the entire period 1992-2008, for which SSM/I data are available.